The Use of Direct Visual Observation as a Means for Learning Leg Movements and Breathing in Butterfly Swimming - Mutaman Jabar Mohamed Hussein (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to examine the effect of direct visual observation on learning leg movements and breathing coordination in butterfly swimming among first-year students. Materials and Methods: This study used an experimental one-group pre-test and post-test design. The sample consisted of 12 first-year students from the College of Physical Education and Sport Sciences, University of Wasit. An eight-week instructional program based on direct visual observation was implemented, with two sessions per week. The program used images, videos, slow-motion demonstrations, and practical pool exercises. Data were collected through leg movement with breathing tests and butterfly stroke performance tests. The data were analyzed using descriptive statistics and paired-samples t-test. Results: The results showed significant improvement between the pre-test and post-test scores in leg movement with breathing, butterfly stroke achievement, and technical performance evaluation. The post-test scores were higher than the pre-test scores, indicating that direct visual observation improved students’ understanding, movement coordination, and technical execution. Conclusions: Direct visual observation was effective in improving the learning of butterfly swimming skills, especially the coordination between leg movements and breathing. This method can be recommended as an instructional aid in swimming education and other motor skill learning contexts.